THEMATIC PROGRESSION IN JAKARTA POST AND ‘KOMPAS’ NEWSPAPER EDITORIALS: A COMPARATIVE STUDY ON TEXT COHERENCE STRATEGY - Neni Triyana; Safnil Arsyad; Arono Arono (JOALL (Journal of Applied Linguistics and Literature), 2018)
This research objective are analyze the common pattern in Jakarta Post and ‘Kompas’ newspaper editorials. The research method used was a mixed method. The research instrument is checklist. The procedure classifies all objects (10 texts Jakarta Post newspaper editorials and 10 texts ‘Kompas’ newspaper editorials) on the thematic progression patterns are checklist. The result showsthat the thematic progression in Jakarta Post and ‘Kompas’ newspaper editorials are found 3 patterns of thematic progression; 10 texts derived theme; 8 texts Constant progression, and 2 text linear progression. The different on thematic progression in Jakarta post and “Kompas’ newspaper editorials is  difference,the difference of sequence in the patterns between Jakarta Post and ‘Kompas’ newspaper editorials. The Conclussion Thematic Progression in Jakarta Postand ‘Kompas’ newspaper editorials are derived theme and Constant progression.